Imperative of Entrepreneurship Education for University Students: The Case Study of University of Ibadan - Yomi-Akinola, Olubukola G.; Adedapo, Adeolu A. (Unilag Journal of Humanities, 2019)
The renewed interest in the study and practice of entrepreneurship in the 21st century is due to its potency to create business, boost productivity, and increase wealth, as well as its capacity to effect positive change in market or industry structure in particular and the society in general. Entrepreneurship education became compulsory for all undergraduates of Higher Educational Institutions in Nigeria effective from 2007/2008 academic session with a view to re-orientating graduates towards entrepreneurial selfefficacy, value creation and self-employment. This study assesses the beneficial impact of entrepreneurship education on University of Ibadan (UI) students. The research deploys both theoretical and conceptual frameworks of Entrepreneurship, and follows the trends in entrepreneurship value and development. A population of all students who have passed through GES 301, both GES 301 and ETR 301, or are doing M.Sc. in Entrepreneurship was involved. Samples were drawn using the purposive sampling technique via an online survey, created through Google Forms. A sample size of one hundred and two was involved. The research findings justify the inclusion of entrepreneurship education in the curricula of UI.